Religious Activism on Campuses in Togo and Benin - Madore, Frédérick (De Gruyter, 2025)
This book examines the history of Christian and Muslim student associations at the universities of Lomé (Togo) and Abomey-Calavi (Benin) since the 1970s. It traces their emergence under authoritarian regimes and examines their impact on the secular nature of these public institutions. In the face of rising university enrolments and graduate unemployment, these groups now offer a "social curriculum" that goes beyond religious guidance.